The relation of oratory to literature - Woestemeyer, Frederick Otto (My University, 1899)
Introduciton: Any art, whether it be painting, music, sculpture, literature, or eloquence necessarily bears a relation to every other art; for art of every form is the expression of some great thought or emotion; and in the arts are summed up the highest and best of man’s nature. Art of every form appeals to the spirit, the highest and best of man, and if responded to, fills him with the desire to become nobler and better. Literature, as implied above, is one of the means of expressing the highest thoughts of man. It includes all thoughts that possess universal value, and are well expressed. De Quincey and other writers divide literature into two classes: first the literature of knowledge; and secondly, the literature of power. By the same writers, the function of the first is said to be to teach; and the function of the second, to move.
Citation: Woestemeyer, Frederick Otto. The relation of oratory to literature. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Oratorical Literature; Field of Oratory; Kinds of Oratory; Theses; Manuscripts (documents)